LIVER AND SPLEEN XENOEXTRACTS APPLICATION IN COMPARISON WITH CRYODESTRUCTION IN EXPERIMENTAL CIRRHOSIS TREATMENT - Olefirenko, O.O.; Sleta, I.V.; Galchenko, S.E. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Processes of regeneration of the cirrhotic liver after cryodestruction and intraperitoneal injection of the extracts of liver and spleen from new-born piglets to rats have been studied. It has been shown that either applied methods acts on the reparation process in liver tissue. The studied methods can stop and reverse the cirrhotic process.